2006
DOI: 10.1102/1470-7330.2006.0016
|View full text |Cite
|
Sign up to set email alerts
|

The use of MRI in planning radiotherapy for gynaecological tumours

Abstract: Parameters that significantly influence results in radiation treatment of gynaecological malignancies are mainly related to the tumour characteristics and the radiotherapy technique used. High-dose radiotherapy requires accurate localisation of the tumour volume and its relationship to surrounding normal tissues. For many years the standard technique used for irradiation of the pelvic area was the four-field box technique which offered the potential benefit of the lateral fields to shield the rectum and small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…There are obvious potential advantages of including image registration in the treatment planning process [21], but historically, technical issues associated with MRI distortion, artefacts and lack of electron density information, along with little evidence of its positive effect on patient outcome, are likely to have precluded its universal use in treatment planning [22]. Despite these issues, studies have demonstrated the feasibility of pelvic image registration for RT treatment planning [23][24][25][26].…”
mentioning
confidence: 99%
“…There are obvious potential advantages of including image registration in the treatment planning process [21], but historically, technical issues associated with MRI distortion, artefacts and lack of electron density information, along with little evidence of its positive effect on patient outcome, are likely to have precluded its universal use in treatment planning [22]. Despite these issues, studies have demonstrated the feasibility of pelvic image registration for RT treatment planning [23][24][25][26].…”
mentioning
confidence: 99%
“…CT would be a reasonable alternative if MRI based planning is unavailable, given that vivid soft-tissue detail and accurate reconstructions can be had with helical CT-scanners. [910]…”
Section: Discussionmentioning
confidence: 99%
“…However, because MRI is not widely available at this time, most planning occurs with CT. The appropriate position of the HDR probe distal tip should be within the endometrial cavity; if using MRI, this positioning is best evaluated on sagittal T2-weighted images [36]. The intracavitary device should be centered at the level of the tumor.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…MRI has become the method of choice for image-guided intracavitary brachytherapy given improved soft tissue contrast of normal structures and associated tumor [22,23,36]. However, because MRI is not widely available at this time, most planning occurs with CT.…”
Section: Endometrial Cancermentioning
confidence: 99%